Adaptive super-twisting nonsingular fast terminal sliding mode control for cable-driven manipulators using time-delay estimation. (February 2019) - Wang, Yaoyao; Zhu, Kangwu; Yan, Fei; Chen, Bai
Highlights: Propose a novel AST-NFTSM control scheme with TDE technique. Prove the stability of the closed-loop control system with AST and NFTSM dynamics; Demonstrate the validity of proposed method through both simulations and experiments. Abstract: To guarantee high-precision trajectory tracking control of cable-driven manipulators under complicated unknown uncertainties, we propose a novel adaptive super-twisting nonsingular fast terminal sliding mode (AST-NFTSM) control scheme using time-delay estimation (TDE) in this paper. The proposed TDE-based AST-NFTSM control scheme mainly contains three terms: a TDE term used to estimate and compensate the remaining lumped system dynamics; an AST term applied to ensure fast convergence and strong robustness in the reaching phase; and a NFTSM term utilized to guarantee fast convergence and high precision in the sliding mode phase. Thanks to the TDE scheme, no system dynamics are required and a fascinating model-free feature is achieved. In the meantime, fast convergence and high precision and strong robustness can be effectively ensured using the AST and NFTSM terms. The stability of the closed-loop control system is analyzed using Lyapunov method. Finally, the validity and superiorities of our newly proposed TDE-based AST-NFTSM control scheme were demonstrated through comparative 2-DOFs (degree of freedoms) simulation and experiments.